ASPEK OPTIMISME SEBAGAI REALISASI NILAI NASIONALISME - Purnama, Sasmitaningtyas Citra; Wisudawanto, Rahmat; Anggitia, Paramastu Titis (KOMUNITAS, 2014)
Nowdays, the improvement of nasionalism is needed.  One of them is the pround feeling throught our  national  football.  In  motivation  national  football  team  player.  It  is  needed  to  sing  a  song which has nasional theme. One of them is Garuda di Dadaku. This research is aimed to identify and to classify optimism aspects in Garuda di Dadaku and also to describe denotative and conotative meaning and also mitos based on those aspects. This  rescach  belongs  to  descriptive  qualitative,  the  source  of  data  is  the  lyrics  of  Garuda  di Dadaku, where as data in this research in all of phrase which consist of optimism aspects. This research used semiotics analysis theory of Roland Barthes. The analysis was done throught three steps, namely denotation level, conotation level and mitos. The results of  analysis shows that there  are three  optimism aspect in  Garuda di Dadaku lyrics. There  are  permanensi,  pervasivitas  and  personalisasi.  Base  on  eleven  data,  the  distribution  to ward the aspect are 6 data consider as permanensi aspects, data classified as pervasivitas aspect and  data  categories  as  personalisasi  aspect.  Where  as  in  mitos  level  data  categories  a  two. Namely proud and pride.